The analysis of determinants of shift nurses’ sleep quality during the COVID-19 pandemic at Sanglah general hospital Denpasar - Gunawan, Stephanie E.; Laksmidewi, Anak Agung Ayu Putri; Gelgel, Anna M.; Adnyana, I. Made Oka; Utami, Desak Ketut Indrasari; Budiarsa, I. Gusti Ngurah (International Journal of Advances in Medicine, 2021)
Background: Fatigue and sleepiness experienced by nurses can put them at risk of making mistakes in medication administration and clinical judgment. In addition, fatigue and sleepiness can also lead to increased emotions towards co-workers, jeopardize their own safety, especially on the way home from work, and can reduce patient care. Methods: This study used an analytical research method with a cross-sectional study, involving 91 shift nurses. It was carried out by conducting interviews during the first break of the first morning cycle after holiday. Results: Results of this study indicated that all sociodemographic variables did not show significant differences with sleep quality variable with a significance level of p>0.05. There was also no relationship between physical activity and caffeine intake and sleep quality. Moreover, there was no significant difference between physical illness and sleep quality. Sleep quality (Pittsburgh sleep quality index/PSQI) and sleepiness level score (Karolinska sleepiness scale/KSS) showed no significant relationship with p<0.05. KSS was divided into 2 including non-sleepy state (1-6) and sleepy state (7-9).4 Insignificant relationship was also shown between sleep quality score (PSQI) and fatigue level score (fatigue severity scale/FSS). Importantly, insignificant relationship was shown between sleep quality score and hospital anxiety and depression scale. In addition, there was only work unit in COVID-19 isolation room which had a significant relationship to sleep quality compared to non-isolation room with a significance level of p<0.05. Conclusions: Based on results of this study, it can be concluded that work unit in COVID-19 isolation room had a relationship with sleep quality of shift nurses who work in the unit.